2012
DOI: 10.1073/pnas.1113503109
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanism for long-term contrast adaptation

Abstract: To optimize perception, neurons in the visual system adapt to the current environment. What determines the durability of this plasticity? Longer exposures to an environment produce longer-lasting effects, which could be due to either (i) a single mechanism controlling adaptation that gains strength over time, or (ii) long-term mechanisms that become active after long-term exposure. Using recently developed technology, we tested adaptation durations an order of magnitude greater that those tested previously, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(131 citation statements)
references
References 41 publications
12
118
1
Order By: Relevance
“…Here, we show that the effect of prolonged visual stimulation can last for Ͼ1 h in the thalamus. Moreover, psychophysical studies have described a relationship between stimulus duration and recovery time from adaptive effects, termed the duration-scaling law (Bao and Engel 2012;Greenlee et al 1991;Greenlee and Magnussen 1987;Leopold et al 2005), which is consistent with our measurements from thalamic neurons (Fig. 1E).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Here, we show that the effect of prolonged visual stimulation can last for Ͼ1 h in the thalamus. Moreover, psychophysical studies have described a relationship between stimulus duration and recovery time from adaptive effects, termed the duration-scaling law (Bao and Engel 2012;Greenlee et al 1991;Greenlee and Magnussen 1987;Leopold et al 2005), which is consistent with our measurements from thalamic neurons (Fig. 1E).…”
Section: Discussionsupporting
confidence: 77%
“…However, psychophysical studies have also shown a number of adaptations and afterimage effects that can last for hours to months following induction (Bao and Engel 2012;Jones and Holding 1975;McCollough 1965). Here, we show that the effect of prolonged visual stimulation can last for Ͼ1 h in the thalamus.…”
Section: Discussionmentioning
confidence: 75%
“…7), even though similar stimulus parameters have been demonstrated to produce perceptual aftereffects with fore-aft translation ) and with roll ). Large differences in the duration of the adapting and test stimuli have also been shown to induce aftereffects in several other sensory stimuli including visual (Hershenson 1993;Leopold et al 2005;Bao and Engel 2012) and auditory motion (Neelon and Jenison 2004). A general theme in sensory aftereffects is that a longer period of adaptation leads to a stronger and longer aftereffect (Taylor 1963;Greenlee et al 1991;Anstis et al 1998;Neelon and Jenison 2004), but the current data presents a rare exception to this, at least when the test stimulus and adapter are different durations.…”
Section: Tablementioning
(Expert classified)
“…This suppression (as predicted by the optical cause of his diplopia) varied between his left and right eyes, suggesting a neural locus relatively early in the visual pathway. This plasticity does not seem to be limited to perceptual distortions that occur in early childhood: short-and long-term modulation of contrast sensitivity specific for location and orientation in adulthood have also been noted as a consequence of altered video input over various timescales [79,80], and normally sighted individuals show adaptation to the amount of blur in a sequence of images [81]. Thus, it seems plausible that analogous suppressive mechanisms might minimize the perceptual salience of 'comet' trains resulting from axonal stimulation.…”
Section: Ii) Contrast Suppressionmentioning
confidence: 99%